Pilot-scale demonstration of advanced adiabatic compressed air energy storage, Part 1: Plant description and tests with sensible thermal-energy storage. (June 2018) - Geissbühler, L.; Becattini, V.; Zanganeh, G.; Zavattoni, S.; Barbato, M.; Haselbacher, A.; Steinfeld, A.
Highlights: Pilot-scale demonstration of advanced adiabatic compressed air energy storage. Compressed air stored in mostly unlined rock cavern. Thermal energy stored in packed bed of rocks. Estimated plant efficiencies of 63–74%. Abstract: Experimental and numerical results from the world's first advanced adiabatic compressed air energy storage (AA-CAES) pilot-scale plant are presented. The plant was built in an unused tunnel with a diameter of 4.9 m in which two concrete plugs delimited a mostly unlined cavern of 120 m length. The sensible thermal-energy storage (TES) with a capacity of 12 MWhth was placed inside the cavern. The pilot plant was operated with charging/discharging cycles of various durations, air temperatures of up to 550 °C, and maximum cavern gauge pressures of 7 bar. Higher pressures could not be reached because of leaks that were traced mainly to the concrete plugs. Simulations using a coupled model of the TES and cavern showed good agreement with measurements. Cycle energy efficiencies of the TES were determined to lie between 76% and 90%. The estimated round-trip efficiency of the pilot plant was based on the measured TES performance and estimated performances of the other components, yielding values of 63–74%, which compares favorably with the usually quoted values of 60–75% for prospective AA-CAES plants.